Cluster evolution mechanisms during aging in Al–Mg–Si alloys. (15th January 2016) - Fallah, Vahid; Langelier, Brian; Ofori-Opoku, Nana; Raeisinia, Babak; Provatas, Nikolas; Esmaeili, Shahrzad
Abstract: Using Atom Probe Tomography (APT) and Phase Field Crystal ( PFC ) modelling, the early-stage precipitation phenomenon is investigated for naturally- and artificially-aged Al–Mg–Si alloys of two different Mg/Si ratios, i.e. 1 and 2. It is shown that, regardless of alloy composition and aging history, the earliest precipitates appear as finely-dispersed Si-rich clusters which gradually undergo a simultaneous coarsening and Mg-enrichment. In addition, the energetic factors for the instability of natural aging clusters are analysed. The energy analysis also suggests that the initial Si-enrichment of the earliest precipitates is due to the affinity of locally-strained areas for higher Si concentrations when achieving a meta-stable equilibrium with the strain-free surrounding matrix. The subsequent Mg-enrichment is shown to be energetically necessary for an evolving precipitate to survive and grow. The alloy with smaller Mg/Si ratio shows a delay in the onset of Mg-enrichment during natural aging, which is attributed to the higher average Si content, as well as the slow kinetics of diffusion at natural aging temperatures. It is shown that this alloy exhibits a smaller nucleation barrier and critical nucleus size as well. We suggest that the above described mechanisms govern the evolution of early-stage clustering in the common range of age-hardenable Al–Mg–Si alloy compositions. Graphical abstract: